A preliminary investigation of attachment style and inflammation in African-American young adults. Issue 1 (2nd January 2019) - Ehrlich, Katherine B.; Stern, Jessica A.; Eccles, Jacquelynne; Dinh, Julie V.; Hopper, Elizabeth A.; Kemeny, Margaret E.; Adam, Emma K.; Cassidy, Jude
ABSTRACT: Individuals' social experiences are associated with their mental health, physical health, and even mortality. Over the last 30 years, researchers have examined the ways in which these social experiences might be associated with chronic inflammation – a component underlying many of the chronic diseases of aging. Little research, however, has examined the role of adults' attachment style as a specific social component that might be associated with inflammation. In the present study, we utilized data from a sample of 59 African-American adults from the Maryland Adolescent Development in Context Study (MADICS) to examine the links between attachment avoidance and attachment anxiety and C-reactive protein (CRP) and interleukin (IL)-6. After controlling for demographic characteristics, body mass index, and depressive symptoms, attachment avoidance and anxiety were associated with IL-6 but not CRP. This study adds to the growing body of research identifying the wide range of social experiences associated with inflammation and further suggests that attachment relationship experiences may have implications for biological processes relevant to many chronic diseases of aging.